Development of a new computer program to assess dietary intake among Portuguese school-age children: a qualitative approach - Carvalho, M.A. (2014)
Introduction: Twenty-four-hour dietary recall is the method of choice for assessing food intake among school-age children. Because they require highly trained interviewers, recalls are expensive and impractical for large-scale nutrition research. A new method for assessing dietary intake in children is being developed: the Portuguese self-administered computerized 24-hour dietary recall (PAC24). Objectives: To identify and select food items to comprise PAC24; to better understand the way children report their food consumption on the previous day; and, to know the different meanings and labels children give to some specific food items. Methods: Data were collected through 21 Focus Groups (FG), conducted in 7 primary schools from the 7 regions of Portugal in 2011. 204 children from second to fourth grade participated. FG were homogeneous for children’s grade and area of residence and heterogeneous for gender and socioeconomic status. Children participated in FG after parent’s written informed consent. Topics for discussion were food consumption on the previous day and individual meanings and labeling of some specific food items. Content analysis followed a thematic coding process. Results: A total of 3959 food items were identified and classified into 12 food groups. Children generally reported foods chronologically organized by the three main meals (breakfast, lunch and dinner). Snacks and candies consumption were reported after prompting for snacks and forgotten foods. Not all children were able to record foods successfully; both descriptions and quantities of food posed problems. Different regional culture-specific terms were identified for some of the food-items. Conclusions: This qualitative approach enriched the food-items pool that was originally developed by literature review and revealed the main aspects that should be taken into account in PAC24 development